A iniciação à docência de jovens professores na universidade. - Feldkercher, Nadiane (2015)
This research aimed to investigate, analyze and study theoretically young beginning university professors. The objective was to understand who they are, how they become teachers, and how they interact with their students in class. As a quantitative research, it happened at the Federal University of Pelotas. The data were collected through class observation, questionnaire for students, and interviews with six young beginning professors. The professors, aged 32 or less, had at most 2 years and 7 months of teaching experience, and had not taken a teaching course. They were recent doctors that started their university teaching career after finishing graduation and post-graduation courses. The data analyzed were interpreted and discussed based on the theories about higher education, university teaching, and teaching initiation. The main references used were Cunha (1988, 1991, 2010b), Feixas (2002), Flores (2009), Marcelo García (1999, 2009a, 2009b), Mayor Ruiz (2007, 2009b), Pimenta and Anastasiou (2002) and Zabalza (2004). The categories of analysis and discussion were: the transition from student to professor; the fact that the professors were young; the graduation students; professors’ experiences as students; professorstudent relationship; the process of learning how to teach and the lessons developed by those professors. Based on this study, it is possible to affirm that young beginning university professors become teachers through the discoveries and challenges they face while teaching, the recollection of student experiences, the relationship they establish with their students, the positive and negative examples of teachers, the insecurities and motivations to teach. Thus, they have intense experiences, but keep the personal and professional balance.